2011
DOI: 10.1111/j.1365-2516.2011.02552.x
|View full text |Cite
|
Sign up to set email alerts
|

Factor IX replacement to cover total knee replacement surgery in haemophilia B: a single‐centre experience, 2000–2010

Abstract: Total knee replacement (TKR) is a well recognized treatment for haemophilic arthropathy. Successful haemostasis can be achieved by bolus doses or continuous infusion (CI) using either recombinant (r) or plasma-derived (pd) factor IX (FIX). We retrospectively analysed our experience of factor replacement to cover TKR in haemophilia B patients and explored factors related to FIX use during surgery. Between 2000 and 2010, 13 primary TKRs were performed in 11 haemophilia B patients. Operations were performed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 15 publications
3
27
0
Order By: Relevance
“…To some extent, two key concerns continue to present challenges to the current factor replacement approaches -treatment-related thrombogenicity and formation of inhibitor antibodies against FIX. Thrombosis has been reported following use of plasma derived or rFIX replacement by continuous infusion [10,21,22]. Neither the current nor the previous BAX326 study [5] showed any indication of thrombotic events.…”
Section: Discussionmentioning
confidence: 97%
“…To some extent, two key concerns continue to present challenges to the current factor replacement approaches -treatment-related thrombogenicity and formation of inhibitor antibodies against FIX. Thrombosis has been reported following use of plasma derived or rFIX replacement by continuous infusion [10,21,22]. Neither the current nor the previous BAX326 study [5] showed any indication of thrombotic events.…”
Section: Discussionmentioning
confidence: 97%
“…[4] Furthermore,, in hemophilia B patients that receive continuous infusion of FIX for surgery, the amount of FIX required to maintain a level of 100% decreases with time—as though one were saturating binding sites. [5] These data suggest the existence of a significant extravascular FIX compartment.…”
mentioning
confidence: 91%
“…Information on 31 selected JA concerning 35 studies on HB and/or FIX is provided in Table . Overall 21 published studies (60.0%) were related to FIX, of which 17 (48.6%) were on safety, efficacy and/or pharmacokinetics of different FIX products , two studies on dosing , one on allergic reactions and one on use of FIX worldwide . HB was the focus of seven studies, of which three studies compared features of HA or FVII deficiency to HB, two studies on correlation between genotype and phenotype of HB , one registry on incidence of inhibitors, allergic and anaphylactic reactions and one study on the global prevalence of HB .…”
Section: Resultsmentioning
confidence: 99%